REINTERPRETASI MAKNA WALAD DALAM KEWARISAN CUCU DITINJAU DARI PERSFEKTIF USHUL FIQH - Nasution, Adelina (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2017)
Surah an-Nisa, verses 11, 12 and 176 are the basis for inheritance. Those verses explain the word walad. The scholars agree that the word walad in surah an-Nisa, 11 refers to son and daughter. However, scholars differ when interpreting the word walad in surah an-Nisa, 176. First, majority of scholars opine that the word walad here refers to only son. Second, Ibn Abbas comes to a conclusion that word walad in the verse refers to both son and daughter. When viewed from the perspective of ushul fiqh by the term the word used, there are two kinds of meanings of words, namely literal and figurative meaning. The literal meaning of the word walad refers to children, while the figurative meaning of the word includes the meaning of grandchildren. Based on the Arab kinship system, the majority of Muslim scholars say that grandchildren are only those from male lineage. Based on the figurative meaning, the grandchildren inherit the same portion as those of children. As also explained in the Compilation of Islamic Law (KHI), article 185, grandchildren can be the heirs of successors, meaning that grandchildren replace the position of their fathers when passing away. However, the position of grandchildren from the female lineage is not explicitly stated in the article. For the sake of justice, grandchildren from the female lineage also are also included as the heir.